Avaliação de diferentes doses de NPK na dinâmica da composição florística e análise bromatológica do campo nativo, em Dom Pedrito - RS - (:unkn) unknown (Universidade Federal do Pampa, 2018)
Brazil is one of the largest producers of beef in the world, in recent years the country was ranked second in terms of production, behind the United States (FAO 2013). The native field has a seasonality of production so one must find ways to improve the productivity of the field. In this sense, the objective of the present work was to evaluate the effects of different doses of NPK on the dynamics of floristic composition and quality in the native field in the municipality of Dom Pedrito, RS. The experiment was conducted in the rural area of the Federal University of Pampa (UNIPAMPA) of the Dom Pedrito campus, commonly called "Estância do Pampa". The experimental area consisted of sixteen plots of 49 m² each, in four levels of fertilization applied to the haul, being: 0 (control), 150, 300 and 450 kg / ha, in the floristic survey conducted in the autumn were identified 41 species (Figure 6), distributed in 11 families, 36 families and 9 species were identified in winter. It was observed a greater representativeness of some species for both, being these: Sporobolus indicus, Paspalum notatum, Desmodium incanum, Flat Eragrostis, Axonopus affinis. In the evaluation of the treatments with and without mowing, there was a greater difference for dead biomass where the CR obtained lower levels. There was an increase in height as the doses of NPK were increased. In the bromatological analysis, the percentage of crude protein increased in the treatments of 0, 150 and 300 kg / ha, which obtained, respectively, 9.05%, 9.2% and 11% of CP, fertilization at the level of 150kg / ha presented no significant difference in relation to the treatment without fertilization. The percentage of NDF had a reduction of the fibrous material of the pasture, which improves the digestibility, presenting in the treatment 0 (71.74%) the highest content and decreasing the level of fertilization, 150 (56.04%), 300 (51, 04%) and 450 (48.45%) kg / ha. For the levels of Dry Matter a constant decrease is observed as the levels of fertilization increase. It is possible to conclude that among the levels of fertilization evaluated, the one that presented the best numerical results in relation to the crude protein was the treatment with 300 kg / ha. Among the floristic assessments, the fall period obtained more species as well as families.
Keywords: Adubação; Composição botânica; Composição Bromatológica; Fertilizing; Botanical composition; Bromatological composition; CNPQ::CIENCIAS AGRARIAS